An interactive procedure to improve estimate of value efficiency in DEA - Gerami, Javad (Expert systems with applications, 2019)
•The concept of value efficiency introduced in data envelopment analysis.•The novel algorithm proposed for calculating the value efficiency.•A new approach comes to incorporating preference information in the process of evaluating efficiency.•The value efficiency is calculated based on input and output components.•The method has been applied for real world data. Value efficiency analysis is an approach to incorporate the Decision-Maker's (DM) priori knowledge (preference information) into efficiency analysis. This paper presents a multi-objective programming model to measure the value efficiency. The model's feasible region is the production possibility set in data envelopment analysis (DEA) and the objective functions are the value efficiency scores corresponding to input and output components. Considering the structure of the proposed model and the concept of value efficiency, the step method (STEM) method to solve the model and gain the value efficiency is used in this paper. By selecting MPU (most preferred unit) units based on the manager's choice, the suitable benchmarks and value efficiency scores could be obtained corresponding to the unit under evaluation, then one could see that the obtained benchmarks and value efficiency scores are strongly dependent on the selected MPU units. Finally, a numerical example is proposed to illustrate the credit of the proposed approach. The method has been applied for real world data.